The structure and evolution of a forming galaxy cluster at z = 1.62 - Hatch, Nina A.; Muldrew, Stuart I.; Cooke, Elizabeth A.; Hartley, William G.; Almaini, O.; Simpson, C.J.; Conselice, Christopher J. (Oxford University Press, 2016)
We present a comprehensive picture of the Cl 0218.3−0510 protocluster at z = 1.623 across 10 comoving Mpc. Using filters that tightly bracket the Balmer and 4000 Å breaks of the protocluster galaxies we obtain precise photometric redshifts resulting in a protocluster galaxy sample that is 89 ± 5 per cent complete and has a contamination of only 12 ± 5 per cent. Both star-forming and quiescent protocluster galaxies are located, which allows us to map the structure of the forming cluster for the first time. The protocluster contains six galaxy groups, the largest of which is the nascent cluster. Only a small minority of the protocluster galaxies are in the nascent cluster (11 per cent) or in the other galaxy groups (22 per cent), as most protocluster galaxies reside between the groups. Unobscured star-forming galaxies predominantly reside between the protocluster’s groups, whereas red galaxies make up a large fraction of the groups’ galactic content, so observing the protocluster through only one of these types of galaxies results in a biased view of the protocluster’s structure. The structure of the protocluster reveals how much mass is available for the future growth of the cluster and we use the Millennium Simulation, scaled to a Planck cosmology, to predict that Cl 0218.3−0510 will evolve into a 2.7+3.9 −1.7 × 1014M cluster by the present day.